2000
DOI: 10.1023/a:1008348704373
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine and vinorelbine in pretreated advanced breast cancer: A pilot study

Abstract: The GEM-VNR combination seems to be active in pretreated ABC with an acceptable toxicity pattern, and may well reppresent an interesting therapeutic choice after anthracycline/taxane regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
15
1
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 5 publications
8
15
1
3
Order By: Relevance
“…For the use of gemcitabine-vinorelbine, an RR of 22∼55.5% and a TTP of 6.8∼9.5 months for first-line and second line treatments have been reported (17)(18)(19). For the use of capecitabine, an RR of 28% and a TTP of 4.9 months for second-line to fifth-line treatment have been reported (20).…”
Section: Discussionmentioning
confidence: 99%
“…For the use of gemcitabine-vinorelbine, an RR of 22∼55.5% and a TTP of 6.8∼9.5 months for first-line and second line treatments have been reported (17)(18)(19). For the use of capecitabine, an RR of 28% and a TTP of 4.9 months for second-line to fifth-line treatment have been reported (20).…”
Section: Discussionmentioning
confidence: 99%
“…The T-gem-vin combination was chosen on the basis of experimental data demonstrating additive or synergistic activity among these drugs (15), and clinical trials confirming the clinical activity and safety of gemcitabine and vinorelbine in previously treated MBC (18)(19)(20)(21). In particular, the results of our previously published phase I-II study suggested that the gemcitabine-vinorelbine combination, using the same schedule and dose tested in this study, is an active and well-tolerated second-line therapy in patients pretreated with both anthracyclines and taxanes (22).…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical data suggest that the combination of trastuzumab with the antimetabolite gemcitabine or the semisynthetic vinca alkaloid vinorelbine has additive or synergistic activity (15). Gemcitabine and vinorelbine have demonstrated satisfactory antitumoral activity as single agents in metastatic breast cancer (16) and, due to the substantial antitumoral activity of the two drugs, different mechanisms of action and favorable toxicological profile, their combined use has been successfully tested for the palliative treatment of advanced (17)(18)(19)(20) and also active in patients with progressive disease after anthracyclines and taxanes (21). Taken together, these pre-clinical and clinical data suggest that the combination of trastuzumab, gemcitabine and vinorelbine is a potentially active and safe treatment for previously treated patients with HER-2/neu-positive MBC.…”
Section: Introductionmentioning
confidence: 99%
“…Two additional studies that applied 4-week regimens of gemcitabine plus vinorelbine, but solely as second-line therapy (after anthracyclines B taxanes), achieved response rates of 48 and 54%, respectively [59,60]. Threeweek regimens using identical schedules but slightly different doses of gemcitabine or vinorelbine as second-or third-line therapy produced lower response rates of 22% [61,62] or 39% [63].…”
Section: Gemcitabine Plus Vinorelbinementioning
confidence: 99%